Pendampingan Literasi Keuangan untuk Meningkatkan Kesadaran Menabung Penerima Bantuan Renovasi Rumah di Desa Sooko, Gresik - Kurniawan, Abraham Ivan; Hadap, Billy Mathew; Sudarsono, Jethson Edbert; Pertiwi, Dewi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
The community of Sooko Village, Gresik, East Java, has yet to fully grasp the significance of financial literacy and saving, primarily due to low income levels and economic uncertainty. This community service initiative aims to enhance financial awareness through training and mentorship. The service-learning method was employed, involving 15 students from Petra Christian University and 3 lecturers, conducted on February 5 and 17, 2025, in collaboration with Habitat for Humanity Indonesia. The activities included lectures, discussions, and the “Quartet” game, designed to teach expenditure prioritization and cash flow management. As a result, participants gained a better understanding of financial management and began to save, despite challenges related to time constraints and the limited number of participants. This initiative is crucial in promoting financial independence through prudent financial management.